2018
DOI: 10.1021/acsomega.8b02393
|View full text |Cite
|
Sign up to set email alerts
|

Iodo-Cycloisomerization of Aryl(indol-3-yl)methane-Tethered Propargyl Alcohols to 3-Iodocarbazoles via Selective 1,2-Alkyl Migration

Abstract: Herein, we disclose the first report on iodo-cycloisomerization of 1-(indol-3-yl)-1-arylbut-3-yn-2-ols to form 3-iodocarbazoles. The synthesis proceeds through a cascade 5-endo-spirocyclization, followed by selective 1,2-alkyl migration. This method governs the green synthesis principles such as open-flask reaction, AcOEt as the solvent, rt reaction with short time, use of iodine, and broad substrate scope with atom and step economy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 70 publications
2
10
0
Order By: Relevance
“…The same phenomenon was found in the iodocycloisomerization of 1-(indol-3-yl)-1arylbut-3-yn-2ols for the synthesis 3-iodocarbazoles, which was reported by Yaragorla et al [45] The existence of an indol-3-yl group allowed a selective 1,2-alkyl migration after the initial 5-endo-dig spirocyclization of propargylic alcohols 195, which was shown in Scheme 39. An acid-catalysed selective synthesis of tetrahydrocarbazoles and carbazoles from (indol-3-yl)pentyn-3ols has been reported by the Baire group in 2018.…”
Section: Tandem Intramolecular Annulations Of Indole-tethered Propargsupporting
confidence: 68%
“…The same phenomenon was found in the iodocycloisomerization of 1-(indol-3-yl)-1arylbut-3-yn-2ols for the synthesis 3-iodocarbazoles, which was reported by Yaragorla et al [45] The existence of an indol-3-yl group allowed a selective 1,2-alkyl migration after the initial 5-endo-dig spirocyclization of propargylic alcohols 195, which was shown in Scheme 39. An acid-catalysed selective synthesis of tetrahydrocarbazoles and carbazoles from (indol-3-yl)pentyn-3ols has been reported by the Baire group in 2018.…”
Section: Tandem Intramolecular Annulations Of Indole-tethered Propargsupporting
confidence: 68%
“…Very short reactiontime, use of green solventand molecular iodine, and post synthetic transformationsa re the major highlights. [40] Continuing their studies on iodine-mediated cycloisomerization reactions, very recently the same group reported am ild and efficient synthesis of 2-iodocarbazoles 136 from very similars tartingm aterials. The authors deliberately substituted the electron-donating indole or trimethoxy group with comparatively less electron-donating phenylr ing in the startingindol-3-yl-but-3-yn-2-ol 133,which directs the selective 1,2-alkenyl migration in the spirocyclic intermediate 134 resulting in the formation of 2-iodocarbazoles as final product.…”
Section: Metamorphosis Of Indole-tethered Propargyl Alcoholsmentioning
confidence: 99%
“…Comprehensive DFT studies also explained the selectivity of the 1,2‐migration in this cascade cyclization‐isomerization process. Very short reaction time, use of green solvent and molecular iodine, and post synthetic transformations are the major highlights [40] . Continuing their studies on iodine‐mediated cycloisomerization reactions, very recently the same group reported a mild and efficient synthesis of 2‐iodocarbazoles 136 from very similar starting materials.…”
Section: Metamorphosis Of Heteroarene‐tethered Propargyl Alcohols Andmentioning
confidence: 99%
“…[76] Iodo-cyclisation of aryl(indol-3yl)methane-tethered propargyl alcohol 194 furnished multisubstituted iodocarbazoles 195 (Scheme 65). [77] The mechanistic cascade includes initial activation of alkyne unit by iodine, 5-endo-spirocyclisation, 1,2-alkylmigration followed by aromatisation to yield the product 3-iodocarbazole 195.…”
Section: Other Benzannulation Reactionsmentioning
confidence: 99%